Peran Pemerintah Mengatasi Perselisihan Dalam Organisasi Advokat di Indonesia - Hikmah Amna Mnr; Syifauzzahrah Syifauzzahrah; Fauziah Lubis (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2023)
The ongoing problem is related to the formation of the PERADI Advocate Organization and the KAI Advocate Organization, where PERADI stated that the organization was the only advocate organization that was legally recognized by law, but this was opposed by KAI with one of the reasons that the establishment of the PERADI Advocate Organization does not comply with applicable regulations. The research method uses a normative juridical approach.The author can conclude that the role of the government as an intermediary in the formation of the forum is formed by the government, but in its management it is still handed back to the Advocates or the advocate organization itself, this is intended to continue to emphasize the role and function of the Advocate as a profession that is free, independent and responsible. Key word: Advocate, government role, organization.